The influence of KCl concentration on the gelation of myofibrillar protein giant squid (Dosidicus gigas) due to molecular conformation change - Niu, Fuge; Ma, Shuang; Zhang, Xiuzhen; Ritzoulis, Christos; Chen, Yueyue; Pan, Weichun (Frontiers in Nutrition, 2023)
Paramyosin has been separated and purified from myofibrillar protein extracted from giant squid; the purification was verified by SDS-PAGE and size exclusion chromatography. Giant squid’s paramyosin molecular mass and intermolecular interactions were quantified by means of light scattering techniques under three KCl concentrations (0.15, 0.5 and 1 mol/L). The obtained apparent molecular weight (ca 2×105 g/mol) suggested that protein molecules existed as dimers, while the second virial coefficient A2 significantly reduced from -3.98456×10-5 to -5.07575×10-4 ml mol/g2 when KCl concentrated from 0.15 to 1 mol/L, indicating the attractive interactions increase. KCl is shown to promote conformational changes to the protein structure. The existence of paramyosin aggregates with their size of salt concentration dependency explained inconsistences in the molecular weight (Mw). Light scattering data also suggest that paramyosin dimers are stiff, with a persistence length of 120 nm, almost the length of a molecule and independent of salt concentration. The micro-rheology study via diffusing wave spectroscopy (DWS) technique revealed that this conformation change dramatically affected myofibrillar protein gelation process. Mean-square displacement (MSD) of tracer particles at 5 temperatures with 4 salt concentrations displayed that this conformation change had dramatic effect. Therefore, G’ and G’’ were remarkably altered with at least one order of magnitude difference owing to this event occurrence.